You are thinking of teaching? : opportunities, problems, realities - Sarason, Seymour Bernard (San Francisco, CA : Jossey-Bass, 1993)
This title discusses: why people choose to become teachers; the changing efforts to reform teacher education; and the factors that have not been considered when developing teacher-training programmes.
Keywords: Teaching -- Vocational guidance; Education -- Study and Teaching